Beyond gatekeeping: Philosophical sources, Indigenous philosophy, and the Huarochirí Manuscript. - Sanchez‐Perez, Jorge (Metaphilosophy, 2024)
This paper argues for a broad definition of philosophical sources and how Indigenous traditional knowledge fits that definition. It concludes by showing how, following the previous two points, an Indigenous document such as the Huarochirí Manuscript can be considered a philosophical source by academic philosophers. The paper has three sections: the first deals with the methodological point of addressing what can be considered as philosophy. This section presents a conversational approach to philosophy. This approach, although broad, properly captures the practices of inquiring about philosophical issues as is commonly done in Western academic circles, but without excluding the practices of non‐Western cultures from being labelled as philosophical. The second section argues for the analytical distinction between a philosophical source, a philosophical text, and a philosophical insight. It shows that what makes a philosophical source such are the philosophical insights that it can provide. The final section shows how the Huarochirí Manuscript has merits making it worthy of being considered a philosophical source and thus a relevant academic source for those working in the field of philosophy.